HIGH-SPEED 5-AXIS MACHINING FOR TOOLING APPLICATIONS - Saxer, M; de Beer, N; Dimitrov, DM (The South African Journal of Industrial Engineering, 2012)
In the modern metalworking industry, production moulds often have complex geometry, with undercut regions, small corner radii, sharp edges, deep cavities, or large cores. Conventional manufacturing process chains to machine these complex features are often lengthy and inefficient due to multiple steps. This article presents current results obtained through industry projects and experimental work using 5-axis high-speed machining with high-end CAD/CAM systems to improve process efficiency. Cost optimisation and lead time shortening can be clearly shown. This is of particular importance for South African manufacturing companies, where multi-axis HSC technology